Kant’s Aesthetic Formalism: Form, Matter, and Judgements of Taste - Deaconu, Alex-Flavius (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
This paper examines Kant’s aesthetic formalism, focusing on the claim that universal communicability in judgements of taste arises solely from the form of objects, excluding sensory content or matter. At the core of this argument is Kant’s concept of “purposiveness without purpose”, which facilitates the harmonious interplay of imagination and understanding. The paper evaluates this formalist approach, addressing Paul Guyer’s critique that colours and tones, traditionally linked to sensory content, can also elicit aesthetic responses, engaging the free play of imagination and understanding. By analysing artworks such as Liza Lou’s Carbon Gunmetal/ Divide, the paper argues that sensory elements enhance form, shaping depth and harmony. It proposes a refined Kantian formalism, where sensory elements gain aesthetic significance only through their contribution to form. Ultimately, the study defends the relevance of Kant’s aesthetic theory for contemporary debates on aesthetic judgement.